Simultaneous and orthogonal covalent exchange processes in dynamic combinatorial libraries - Escalante, Andrea Marta (2010)
In this work, we report the first example of a mixed strategy involving simultaneous and orthogonal covalent reactions in one single system through the combination of the exchange of disulfides, thioesters, and hydrazones. As a consequence of altering the activation order of the sequentially addressable processes,  biased DCLs are obtained where the history of each DCL is manifested as distinct distribution of products.